A CASE STUDY ON APPLICATION OF KSHARASOOTRA IN PILONIDAL SINUS - T.P, *Priya.; Deep, V.C.; Acharya, M.V. (International Journal of Ayurveda and Pharma Research, 2017)
Pilonidal means appertaining to a nest of hair. Pilonidal sinus extends into the subcutaneous planes as an infected track. This occurs predominantly in males at a ratio of 3- 4:1. Incidence of is about 26 per 100,000 population. Disease mainly seen in late teens to early twenties. Sedentary life style and obesity are the contributing factors. It can be correlated with Salyaja nadivrana in Ayurveda and treatment mentioned is Ksharasootra application. In case of surgical treatment main complications are recurrence and post operative infection and wide excision of skin which will take long time to heal. Kshara karma is one of the important parasurgical procedure and Kshara sootra is an effective treatment in case of pilonidal sinus. Kshara sootra helps for cutting, curetting and healing of the tract faster. Kshara is having antimicrobial action so chance of infection is very rare. A case report of pilonidal sinus treated at Central Research Institute, cheruthuruthy is discussed here. Kshara sootra (prepared with Snuhiksheera, Apamarga kshara and Haridra), application was done after preoperative procedures and weekly thread change was done till tract was cut open completely followed by dressing with Jathyadi ghritham. Internally Chiruvilwadi kashaya, Triphala guggulu and Guggulupanchapala choornam was given. Externally sitz bath with Thriphala kashaya daily three times and dressing with sterile pad. Symptoms like pain, discharge, size of wound, unit cutting time was assessed throughout the treatment. Pain and discharge was reduced around 2-3 weeks. Got complete cure around 2 months. Ksharasootra application was found to be effective in pilonidal sinus.